2013
DOI: 10.4103/1319-3767.121033
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative peritonitis without an underlying digestive fistula after complete cytoreductive surgery plus HIPEC

Abstract: Background/Aim:Peritoneal carcinomatosis (PC) is a pernicious event associated with a dismal prognosis. Complete cytoreductive surgery (CCRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) is able to yield an important survival benefit but at the price of a risky procedure inducing potentially severe complications. Postoperative peritonitis after abdominal surgery occurs mostly when the digestive lumen and the peritoneum communicate but in rare situation, no underlying digestive fistula can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
2
5
0
1
Order By: Relevance
“…However, the ratio of deep organ space (CDC definition) infections was higher after HIPEC with mitomycinC/doxorucicin compared to oxaliplatin (30% vs 11%, p=0.028), and two patients in this protocol group had postoperative peritonitis without an underlying digestive fistula, and observation also made by others [25]. This may indicate that, although a rare event, bacterial translocation may contribute to adverse postoperative outcomes.…”
Section: Msupporting
confidence: 53%
See 1 more Smart Citation
“…However, the ratio of deep organ space (CDC definition) infections was higher after HIPEC with mitomycinC/doxorucicin compared to oxaliplatin (30% vs 11%, p=0.028), and two patients in this protocol group had postoperative peritonitis without an underlying digestive fistula, and observation also made by others [25]. This may indicate that, although a rare event, bacterial translocation may contribute to adverse postoperative outcomes.…”
Section: Msupporting
confidence: 53%
“…Overall, in the majority of patients, this effect did not result in a more complicated course. However, it indicates a critical mechanistic step in the pathophysiology of HIPEC and may explain the rare finding of peritonitis without a cause, sometimes observed in patients after HIPEC [25].…”
Section: Mmentioning
confidence: 99%
“…Interestingly, in case of reoperation after CRS and HIPEC, bacterial cultures from intra-operative samples are often positive—regardless of the reason for surgery (infectious or no infectious complication). Moreover Honore’ et al have reported that 13% of postoperative peritonitis after CRS and HIPEC happens without an underlying digestive perforation [ 23 ]. Therefore, some authors have hypothesized a bacterial translocation during HIPEC as the reason for these postoperative septic complications, assuming that traditional antibiotic prophylaxis may be not enough in this complex procedure.…”
Section: Post-hipec Infectious Complications: Current Management and Perspectivesmentioning
confidence: 99%
“…[15]. Die Diagnose der nicht vorhandenen Perforation ist letztlich nur intraoperativ zu stellen, womit sich die Therapie nicht von den zuvor beschriebenen Krankheitsbildern unterscheidet.…”
Section: Peritonitis Ohne Perforationunclassified